Developing an observation instrument for assessing the effectiveness of English teaching at vocational secondary schools - Estu Widodo; Franciscus Xaverius Sudarsono (REID (Research and Evaluation in Education), 2016)
This study was aimed at: (1) developing an observation instrument for assessing English teaching at vocational secondary schools (VSSs), (2) examining the validity of the developed instrument, (3) examining the inter-rater reliability, and (4) assessing the effectiveness of the developed  instrument.  The subjects of the three-phase field-tests were English teachers and students of four VSSs. Observation sheets, questionnaires, and interviewes were employed to collect the data. The instruments were field-tested in three phases. Expert judgment, Kappa Coefficient, and Kane’s (2006) argument-based validation and Bachman Palmer’s intepretive and use argument were used to determine the instrument validity and reliability. The field-test which involved stakeholders prove that the observation instrument could be implemented effectively to assess the teaching of English at VSSs.